The remainder of the division of a polynomial \(P(x)\) by \(x-1\) is 6, and the remainder of the division of \( P (x)\) by \(x + 2\) is 4.Then the remainder of the division of \( P (x)\) by \((x-1 ) (x + 2)\) is:

**(a)**: \(R (x) = 2x / 3 + 16/3\).

**(b)**: \(R (x) = 2x / 3 - 16/3\).

**(c)**: \(R (x) = 2x / 3 + 8/3\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestConsder P(x)=(x-1)(x+2)Q(x)+ax+b;P(1)=6=>a+b=6;P(-2)=4=>-2a+b=4.solve for a,b giving option (a) as remainder.

Log in to reply